Interaction between the Haptoglobin 2 Phenotype and Diabetes Mellitus on Systolic Pulmonary Arterial Pressure and Nitric Oxide Bioavailability in Hemodialysis Patients. (11th June 2015) - Dahan, Inbal; Farber, Evgeny; Thauho, Nadia; Nakhoul, Nakhoul; Francis, Adi; Awawde, Mohamad; Levy, Andrew P.; Kim-Shapiro, Daniel B.; Basu, Swati; Nakhoul, Farid
Abstract : Elevated systolic pulmonary artery pressure (s-PAP, ≥35 mmHg) serves as an independent predictor of mortality in hemodialysis (HD) and diabetic (DM) patients. A polymorphism in the antioxidant Haptoglobin (Hp) gene has been shown to regulate the bioavailability of nitric oxide (NO), a major mediator of pulmonary vascular tone. We therefore set out to test the hypothesis that the Hp polymorphism may be a determinant of developing elevated s-PAP specifically in the DM state due to a decreased bioavailability of NO. To test our hypothesis we Hp typed and performed transthoracic echocardiography on a series of HD patients and stratified them into elevated and normal s-PAP groups and then evaluated whether there was a significant association between the Hp type, elevated s-PAP, and decreased NO bioavailability as defined by low plasma nitrite. We found a statistically significant interaction between the Hp type and DM on the prevalence of elevated s-PAP and lower mean nitrite levels with the combination of elevated s-PAP and low nitrite levels being significantly more prevalent in Hp 2-2 DM individuals. We conclude that the Hp 2 type is associated with elevated s-PAP levels and low plasma nitrite levels in HD patients specifically in the DM state.